Inclusive Leadership as a Strategy for Promoting Educational Rights and Participation of Students with Disabilities - Djedjen Djedjen; Andrian Muhamad; Ika Ismail; Prihantini Prihantini; Juntika Nurihsan (Journal of General Education and Humanities, 2026)
Inclusive education has become a central strategy for ensuring students with disabilities’ educational rights and meaningful participation. Despite significant policy developments and international commitments to disability rights, many students with disabilities continue to encounter barriers that limit their access, participation, and educational success. In this context, educational leadership plays a critical role in promoting inclusive practices and creating equitable learning environments. This study aims to examine inclusive leadership as a strategic approach for advancing educational rights and participation among students with disabilities. The study employed a narrative literature review, analyzing scholarly publications, policy documents, and theoretical works on inclusive education, disability rights, educational leadership, and social justice. The literature was collected from academic databases, including Google Scholar, ERIC, ScienceDirect, and Scopus-indexed journals, and analyzed using thematic analysis. The review identified three major themes: students with disabilities’ educational rights and participation; the theoretical foundations of inclusive leadership; and inclusive leadership as a strategy for promoting educational rights and participation. The findings indicate that inclusive leadership integrates transformational, distributed, and social justice leadership perspectives to foster inclusive school cultures, remove barriers to participation, promote stakeholder collaboration, strengthen teacher capacity, and support equitable educational opportunities. Furthermore, inclusive leadership functions as a bridge between educational rights and meaningful participation by translating policy commitments into inclusive educational practices. The study concludes that inclusive leadership represents a transformative approach to advancing disability rights, educational equity, and social inclusion. Strengthening inclusive leadership is therefore essential for creating educational environments where all students can participate fully and succeed.